Evaluation of the possibilities of using the knowledge capital earnings method (kcetm) for depicting intellectual capital in the annual reports of Polish companies - Anna Bagieńska (e-Finanse: Financial Internet Quarterly, 2019)
Intellectual capital is not sufficiently depicted in the annual reports of Polish companies, although it plays an important role in the operation and market valuation of enterprises. The aim of the paper is to evaluate the possibilities of using the KCETM method for depicting intellectual capital in the enterprise annual report - in particular, in the integrated reports. The KCE method developed by Lev has been modified in the area of normalized revenues, of which the evaluation method is not controlled by the audit, which results in its subjectivity. We adopted the category of gross profit generated by an enterprise from sales (including a large share of costs of earnings) which is reported by the enterprise. On the basis of the financial data from annual reports, we conducted the Knowledge Capital Earnings measurement of selected IT companies and this method was evaluated by comparing the results with the market and financials indicators of the companies and their Market-to-Book Values. The conclusions from the analysis confirmed a strong correlation of intellectual capital (evaluated by modified KCETM method) with market indicators and return on equity. The method of intellectual capital evaluation of Market-to-Book Value did not give results related to market and financial indicators. Therefore, based on the reported gross profit on sales, the KCETM method should be recommended as a measure in the integrated reporting of an enterprise.
Keywords: D24; E22; L21; M21; 330; intellectual capital; KCETM method; annual report; integrated reporting